2020
DOI: 10.1002/2211-5463.12869
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Reduced levels of miR‐485‐5p in HPV‐infected cervical cancer promote cell proliferation and enhance invasion ability

Abstract: Cervical cancer (CC) is the most common gynecological malignancy, with high incidence and mortality rates in China. The microRNA miR‐485‐5p has previously been reported to serve as a negative regulator of tumorigenesis in breast cancer and hepatocellular carcinoma, and miR‐485‐5p has been observed to be differentially expressed between CC and normal control tissue. Here, we confirmed that miR‐485‐5p expression is lower in CC than in adjacent normal tissue and proceeded to investigate the effects of miR‐485 on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A previous study showed that miR‐485‐5p suppressed the invasion of cancer cells by targeting FLOT‐1 in HPV‐infected cervical carcinoma cells 24 . Another study showed that elevated expression of miR‐485‐3p suppressed ki‐67 and cyclin D1 expression in NSCs.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that miR‐485‐5p suppressed the invasion of cancer cells by targeting FLOT‐1 in HPV‐infected cervical carcinoma cells 24 . Another study showed that elevated expression of miR‐485‐3p suppressed ki‐67 and cyclin D1 expression in NSCs.…”
Section: Discussionmentioning
confidence: 99%
“…It inhibited breast cancer progression and chemoresistance through targeting surviving ( Wang et al, 2018a , Wang et al, 2018b ) or MUC1 ( Wang et al, 2020 ). Reduction in miR-485-5p expression in HPV-infected cervical cancer led to an increase in cell proliferation and invasion ( Dai et al, 2020 ). As for in OC, miR-485-5p was found to be poorly expressed in tumors and associated with disease grade ( Kim et al, 2010 ), and as aforementioned, to increase chemosensitivity of OC cells ( Qiao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to our online prediction, there is a binding relationship between LINC01419, miR‐485‐5p, and LSM4. The regulation of miR‐485‐5p on various malignant tumors, such as cervical cancer (CC), 13 renal cell carcinoma, 14 and gastric cancer (GC) 15 has been reported. More importantly, miR‐485‐5p is widely accepted as a tumor suppressor in HCC, 16,17 and its effects on the regulation of HCC cell biological activities can be restrained by lncRNAs through epigenetic regulation 18,19 .…”
Section: Introductionmentioning
confidence: 99%